Integrative taxonomic revision of the Metarctia Walker, 1855 subgenus HebenaWalker, 1856, with descriptions of six new species and one new subspecies(Lepidoptera: Erebidae: Arctiinae: Syntomini) - Fiebig, Ralf; László, Gyula M.; Volynkin, Anton V.; Taberer, Tabitha R. (Zootaxa, 2023)
A revision of the subgenus Hebena Walker, 1856 of the syntomine genus Metarctia Walker, 1855 is given based on integrative taxonomic analyses. Six new species (Metarctia (Hebena) manfredi sp. n., M. (H.) elleni sp. n., M. (H.) brigitta sp. n., M. (H). lukaszi sp. n., M. (H.) smithi sp. n., and M. (H.) haraldsulaki sp.n.) and one new subspecies (M. (H.) smithi transvallesiana ssp. n.) are described. Metarctia (H.) kelleni (Snellen, 1886) stat. rev. is reinstated from synonymy with M. (H.) rubra (Walker, 1856) and Metarctia (H.) subincarnata Kiriakoff, 1954 syn. n. is synonymised with M. (H.) henrardi Kiriakoff, 1953 and Metarctia cinnamomea (Wallengren, 1860) syn. n. with M. (H.) rubra (Walker, 1856). DNA barcodes were obtained for 116 specimens representing 7 taxa, and genetic analyses were performed using Maximum Likelihood and Bayesian Inference approaches; a DNA barcode tree resulting from the latter is illustrated. Pairwise distances of barcodes between taxa are provided where available. The adults and genitalia of all taxa, their habitats and distribution are illustrated in 19 colour plates and 5 distribution maps.